2019
DOI: 10.3354/esr00999
|View full text |Cite
|
Sign up to set email alerts
|

Wanted dead or alive: characterizing likelihood of juvenile Steller sea lion predation from diving and space use patterns

Abstract: Understanding linkages between behaviors and mortality risk is critical for managing populations. Juveniles constitute a particularly vulnerable life stage, with growing evidence that within stages, individual strategies may be associated with greater predation risk and mortality. These forms of predator−prey dynamics are rarely explored in marine environments due to difficulties in confirming vital status of individuals, and the lack of data sets that link mortality to behavior. We analyzed 2 concurrently col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
1
3
1
Order By: Relevance
“…Distance from rookeries and haulouts had a slight positive association with predation risk increasing up to 20 km, but at greater distances the risk diminished again. This finding may appear to contradict the observation by Bishop et al (2019) of slightly elevated predation risk for individuals with increased haulout times during summer, which must occur near rookeries and haulouts, even while overall risk was lower in summer than winter. This disconnect may be due to the differences in temporal scales across studies.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Distance from rookeries and haulouts had a slight positive association with predation risk increasing up to 20 km, but at greater distances the risk diminished again. This finding may appear to contradict the observation by Bishop et al (2019) of slightly elevated predation risk for individuals with increased haulout times during summer, which must occur near rookeries and haulouts, even while overall risk was lower in summer than winter. This disconnect may be due to the differences in temporal scales across studies.…”
Section: Discussioncontrasting
confidence: 67%
“…Overall, between the present study and Bishop et al (2019), the observed diving, haulout, spatial and habitat use associated with resource-risk trade-offs are consistent with a mix of at least two predator types-transient killer whales and Pacific sleeper sharks, as proposed and theoretically modeled by Frid et al (2009). Interestingly, the observations by Bishop et al (2019) that may indirectly suggest closer-to-rookery predation in the summer were derived primarily from telemetered sea lion dive behavior data and were informed by predation event timing, but not location. The positive association of predation risk with deeper bathymetry, and distance from rookeries we report here were derived from predation event telemetry timing and location, and was only spatially constrained by telemetered sea lion movement.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Empirical research shows that there are countless processes underlying both fixed and dynamic condition (e.g. Bishop et al, 2019; Bowen et al, 2015; Gould et al, 2018; Paoli et al, 2020), although some of these processes contribute more often to one type of individual heterogeity than the other. For example, among‐individual variation in genotypes will generally produce fixed condition in vital rates; however, mutations in the genome may lead to dynamic condition.…”
Section: Defining Heterogeneitymentioning
confidence: 99%